Plasma immature form of surfactant protein type B correlates with prognosis in patients with chronic heart failure. A pilot single-center prospective study. (15th December 2015) - Magrì, Damiano; Banfi, Cristina; Maruotti, Antonello; Farina, Stefania; Vignati, Carlo; Salvioni, Elisabetta; Morosin, Marco; Brioschi, Maura; Ghilardi, Stefania; Tremoli, Elena; Agostoni, Piergiuseppe
Abstract: Background: Gas exchange abnormalities are part of the heart failure (HF) syndrome and growing interest raised on possible biomarkers of alveolar–capillary unit damage. The present pilot single-center study sought to investigate the prognostic values of circulating surfactant protein type B (SP-B) in a cohort of systolic HF patients. Methods: One hundred and fifty-one HF stable outpatients and 37 healthy subjects underwent a full clinical assessment, including pulmonary function and lung diffusion for carbon monoxide (DLco), maximal cardiopulmonary exercise test and measurements for both circulating immature and mature forms of SP-B. Study end-points were hospitalization due to HF worsening and cardiovascular mortality. Results: Immature SP-B, but not the mature form, was significantly higher in HF patients than in controls and was independently related to DLco, peak oxygen uptake and ventilatory efficiency. During the follow-up (median: 995 days; interquartile range: 739–1247 days), 97 patients experimented at least one HF hospitalization and 9 died for cardiovascular causes. At univariate analysis immature SP-B levels were significantly related to both cardiovascular death (p = 0.033) and HF hospitalization (p < 0.001). At multivariate analysis, immature SP-B levels remained independently associated to HF hospitalization (hazard ratio: 2.304; 95% confidence interval 1.858–3.019; p < 0.001). Conclusions: Present data confirm a strong relationship between circulating immature SP-B levels, gas exchange abnormalities and exercise limitations in stable HF as well as they are consistent with the use of immature SP-B in HF clinical risk assessment. Larger prospective studies are needed to confirm its prognostic role as well as to evaluate whether immature SP-B plasma concentration varies in response to specific treatment.